Cultured Epidermal Melanocyte Transplantation in Vitiligo: A Review Article - ZOKAEI, Shaghayegh (Iran J Public Health, 2019)
BACKGROUND: The color of the skin is highly heritable but can be influenced by the environments and endocrine factors. Many other factors, sometimes destructive, are also involved in the formation of skin color, which sometimes affects pigmentation patterns. Vitiligo is an autoimmune hypopigmentation painless disorder with appearance of white patches and psychological effects on patients. It is a disease in which melanocytes of the skin are destroyed in certain areas; therefore depigmentation appears. METHODS: We studied more than 60 articles. Several therapeutic methods have been used to return the color of skin in vitiligo. These methods include non-invasive treatment and surgical techniques. Among all these therapies, cell transplantation is an advanced procedure in regenerative medicine. Extraction of melanocytes from normal skin and then their cultivation in the laboratory provides a large number of these cells, the transplanting of which to depigmentation areas stimulates the site to irreversibly produce melanin. RESULTS: The transplantation methods of these cells have been evolved over many years and the methods of producing blister have been changed to the injection of these cells to the target sites. CONCLUSION: In this review, autologous cultured melanocyte transplantation has been considered to be the most viable, safe, and effective method in the history of vitiligo treatments.